Penguatan Konsep Diri dan Pelatihan Konseling Dasar Sebagai Pencegahan Bullying di MI Maarif NU 1 Gunung Lurah - Fakih Hamdani; Galih Yoga Santiko; Ahmad Fauzi; Nur Chamidah; Kuni Safingah (JURPIKAT, 2026)
Bullying in elementary schools has become a serious issue as it affects students’ social and emotional development. This community service focused on bullying prevention by enhancing students’ self-awareness and teachers’ empathetic communication skills. The objective was to build a healthy, safe school ecosystem that supports character development. The program was implemented at MI Ma’arif NU 1 Gunung Lurah using the Participatory Action Research (PAR) approach, involving the school community actively. The strategy included socialization, self-analysis training for students, basic counseling training for teachers, and structured mentoring. The results showed that students were able to recognize themselves, express emotions, and commit to rejecting bullying, while teachers successfully applied empathetic communication and developed simple counseling modules. The impact of this program was evident in the creation of a reflective culture in the classroom through reflection corners, as well as improved openness in interactions between teachers and students.